INTERNET COMMUNICATION TOOLS: THE WAY OF CULTURAL DEVELOPMENT OF PERSONALITY OR FREEDOM OF CHOICE IN THE DIGITAL AGE - E. V. Dyatlova; M. V. Mikhina (Вестник университета, 2019)
With the introduction of almost every sphere of human activity computer technologies, there is a need for the formation of holistic scientific position in determining further cultural development of the human being. An assumption has been made, that a resourceful basis for communication research via the Internet are philosophical categories and cultural-historical psychology, because its statements allow to conceptualize the Internet communication tools as indirect activity. The specific features of electronic interactions, which have a significant impact on development of the of the personality have been highlighted and analyzed in the article: a lack of tactile sensations, increasing the volume and speed of information transfer, the introduction of artificial intelligence in communication tools.